(untitled) (International Journal of Food and Nutritional Sciences, 2022)
LIC of India plays a vital role in the growth of life insurance sector and also to the economic development of the country.Since economic reforms the life insurance sector is changing rapidly due to the continuous change in the customer needs and preferences. These changes have helped in a great number to both the urban and rural consumers. Life Insurance Corporation of India has worked continuously.In order to facilitate their consumers expediently LIC of India has adopted wide-ranging marketing strategies to acquirereach